Innovative Development of Machine-Building Enterprises Based on Cognitive Modeling: Strategic Management Scenarios - Koleshchuk Orest Ya. (Problemi Ekonomiki, 2019)
The aim of the article is determining the level of innovative development of machine-building enterprises based on cognitive modeling for strategic management scenarios. It is found that the formation of scenarios using cognitive technologies is an important method under uncertainty since it allows to determine the boundaries of possible strategic changes in innovative development of machine-building enterprises and effectively manage them. The stages of using the technology of cognitive modeling for the formation of strategic innovation management of machine-building enterprises and the approaches to developing scenarios for the formation of strategic innovation management of machine-building enterprises are considered. It is determined that cognitive maps are used in the process of analyzing and making effective decisions on the formation of strategic innovation management of machine-building enterprises by studying causal relationships between significant factors (notions, concepts). A general cognitive map of strategic innovation management of machine-building enterprises is proposed. At each stage of the formation of the model, decisions, the totality of which determines the flexibility, activity and adaptability of the constructed model, have to be made.